Influence of Growth Need Strength on the Relationship between Work-Family Conflict and Job Satisfaction - Sarkawi, Mohammad Nizam; Shamsuddin, Jauriyah; Jaaffar, Abdul Rahman; Rahim, Noor Fareen Abdul (CENTRAL ASIA AND THE CAUCASUS, 2021)
This study is to determine the influence of Growth Need Strength [GNS] between work-family conflict and job satisfaction among SRN’s. Data were collected through survey using questionnaire. This study employed stratified random sampling involving a total of 390 nurses at selected general hospitals. The finding of the study contributes in the specific area of literature, theory and also in research design. The results of this study suggest that the GNS as moderator have played significant important role between work- family conflict and job satisfaction. It is also providing a much better conducive working environment and by incorporating policies that can improve job satisfaction.